EFFECT OF FOREIGN DIRECT INVESTMENT ON VIETNAM ECONOMIC GROWTH: A TIME-SERIES ANALYSIS - Nguyen, Khanh Huyen (2017)
This study aims at understanding the impact of Foreign Direct Investment (FDI) on the economic growth of Vietnam at national level. In order to achieve the research objectives, this paper takes into account range of economic factors the proportion of implemented FDI to GDP alongside trade openness and growth of exports. The methodology used in this study is the time-series VAR model with optimal lag length of 3 comprising numerous powerful analytical tools: Granger causality test, Forecast error variance decomposition analysis and Impluse response function analysis. Employing the empirical data from the period 1995 to 2016, the model results find that FDI has a significant and positive impact on the economic growth of Vietnam, however, the impact seems to be diminishing over time, implying that FDI could be beneficial in the short term but not in the long term. The paper concludes that in order to fully optimize the potential benefits of FDI, Vietnam’s government needs to set up more effective management and supervision policies together with improved absorptive capacity through human resources development.